A new species in the genus Crisicoccus Ferris (Hemiptera: Coccomorpha: Pseudococcidae), with a key to Chinese species - Zhang, Jiang-Tao; Wu, San-An (Zootaxa, 2016)
A new mealybug, Crisicoccus ziziphus sp. nov. (Hemiptera: Coccomorpha: Pseudococcidae), collected on the leaves and twigs of Ziziphus jujuba (Rhamnaceae), is described from China. All the female developmental stages (adult, third-instar, second-instar and first-instar nymphs) are described and illustrated. Keys are provided to separate the female instars and to identify adult females of Crisicoccus species from China.